Translating Mechanisms of Orofacial Neurological Disorder - Kobayashi, Masayuki (International review of neurobiology, 2011)
In this volume, members of the International Translational Research Network on Orofacial Neurological Disorders and invited experts provide authoritative overviews of new aspects of motor function and sensation relating to neurological disorders in orofacial regions. Orofacial movements constitute fundamental motor patterns with essential roles in consummatory behaviour, self-care, defensive and attack behaviours, vocalisation and, in higher mammals, verbal as well as non-verbal communication. Clinically, dysfunction in orofacial movement is evident in numerous dental, cranio-maxillo-facial and neuropsychiatric disorders, including dysphagia, Huntington's disease, Parkinson's disease and schizophrenia. Leading authors review the state-of-the-art in their field of investigation, and provide their views and perspectives for future research Chapters are extensively referenced to provide readers with a comprehensive list of resources on the topics covered All chapters include comprehensive background information and are written in a clear form that is also accessible to the non-specialist.